RUGI – RUGI DAYA AKIBAT PENGARUH KETIDAK SEIMBANGAN BEBAN TERHADAP ARUS NETRAL PADA EFEKTIFITAS PENGGUNAAN DAYA TERPASANG - Budiyasa, I Gede; Artha Wijaya, I Wayan; Indra Partha, Tjok Gede (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p29, 2021)
The increasing need for electrical power with a stable and continuous distribution of electricity networks is an absolute requirement in meeting the needs of electrical energy. The load imbalance between each phase (phase R, phase S, and phase T) which flows a net current in the transformer, because of the transformer tolerance set by PLN, which is 20% of the power capacity of the transformer In Abiansemal feeders there is a load imbalance of more than 20 % then in this study the load balancing is carried out in the LVMDV panel on three-phase customers, which has an impact on the load imbalance between each phase (phase R, phase S, and phase T) which causes a neutral current and causes losses (losses). Based on this problem, balancing must be done by measuring first. From the measurement results in the LVMDP panel on three-phase customers and data obtained from the results of measurement of load imbalance during the day is 29.9% and 26.6 % and the load imbalance at night is 62.6% and 31%, as shown in Table 4.5, it can be seen that the bush on the large current neutral IN that flows in the transformer neutral conductor, the greater the loss in the neutral conductor (PN).